Opportunities and constraints for developing low-cost aquaculture of seahorses in mangrove estuaries - Cohen, Felipe P.A. [UNESP]; Valenti, Wagner C. [UNESP] (Elsevier, 2019)
Wild populations of seahorses are threatened by overexploitation and the increasing black market to supply the trade of dried specimens for traditional Chinese medicine, religious rituals and other uses. Intensive aquaculture systems, available for seahorses, are developed for producing high-value specimens for marine aquariums, and thus, are not suitable to solve the real threat facing their conservation, which is the market of dried seahorses. Therefore, our aim was to describe opportunities and constraints to develop low-cost aquaculture of seahorses in cages in mangrove estuaries to foster a legal and more sustainable production chain. A comprehensive review in literature was performed followed by trials throughout one year in a sub-tropical mangrove estuary to observe the strengths and weakness of low-cost systems set up in mangroves. In these systems, seahorses should grow-out relying only on wild plankton and periphyton available in the estuary. We discuss that the production of seahorses in mangrove areas has many opportunities to increase environmental and social sustainability. Nonetheless, we also addressed the main constraints of this production that should be overcome to establish a reliable culture protocol, including the environmental instability of estuaries, net obstruction, predators and escapees.
Keywords: Ecological aquaculture; Extensive aquaculture; Hippocampus; Longsnout seahorse